Diet of juvenile skipjack herring Alosa chrysochloris : Ontogenetic shifts, predator–prey size ratios and mouth gape allometry - Joshua P. Egan; Peter J. Hundt; Neil P. Rude; Jason A. DeBoer; Benjamin J. Lubinski; Kristopher A. Maxson; Levi E. Solomon; Andrya L. Whitten Harris; Andrew M. Simons (Journal of Fish Biology, 2026)
The skipjack herring Alosa chrysochloris inhabits Gulf of Mexico drainages, primarily the Mississippi River Basin, and estuarine environments in the Gulf of Mexico. The trophic ecology of the skipjack herring is poorly understood, therefore we quantified the length, mouth gape and gut contents of juvenile skipjack herring from the Mississippi River (fish n = 6), Illinois River (fish n = 181) and Ohio River (fish n = 255) and tested for changes in diets and predator–prey size ratios during ontogeny. We identified statistically significant changes in prey type consumption during ontogeny. Aquatic insects dominated the diets of skipjack herring 40 mm SL were primarily composed of fishes. The most prevalent fish species consumed by skipjack herring were invasive bigheaded carps Hypophthalmichthys spp. and preliminary evidence indicated that inter‐annual variation in the consumption of bigheaded carps was driven by variation in juvenile bigheaded carp abundance. Additional research is needed to determine if the enhancement of native skipjack herring populations could be used as a tool to limit bigheaded carp population sizes. Skipjack herring SL and mouth gape were both significantly positively correlated with maximum, median and minimum sizes of prey consumed. There were allometric changes in the mouth gape of juvenile skipjack herring, with the ratio of mouth gape to SL increasing until ~80 mm SL, then gradually declining. Maximum mouth gape to SL ratios corresponded to substantial increases in the consumption of fishes, indicating that mouth gape allometry may facilitate the ontogenetic transition to piscivory in the skipjack herring. This study improves our understanding of skipjack herring ecology and provides data that can be incorporated into future ecological and evolutionary research, such as the development of food web models.

Correction to: Smallmouth buffalo (Ictiobus bubalus Rafinesque) population trends and demographics in the Upper Mississippi River System - Kristopher A. Maxson; Levi E. Solomon; Taylor A. Bookout; Steven A. DeLain; Andrew D. Bartels; Melvin C. Bowler; Eric J. Gittinger; Eric N. Ratcliff; John L. West; Seth A. Love; Jason A. DeBoer; Andrya L. Whitten‑Harris; et al. (Environmental Biology of Fishes, 2024)

Population structure and vital rates of Shortnose Gar Lepisosteus platostomus in a large floodplain river - Sarah A. Molinaro; Sarah M. King; Levi E. Solomon; Kristopher A. Maxson; Jeffrey A. Stein (Environmental Biology of Fishes, 2024)

Smallmouth buffalo (Ictiobus bubalus Rafinesque) population trends and demographics in the Upper Mississippi River System - Kristopher A. Maxson; Levi E. Solomon; Taylor A. Bookout; Steven A. DeLain; Andrew D. Bartels; Melvin C. Bowler; Eric J. Gittinger; Eric N. Ratcliff; John L. West; Seth A. Love; Jason A. DeBoer; Andrya L. Whitten-Harris; et al. (Environmental Biology of Fishes, 2024)
Smallmouth buffalo ( Ictiobus bubalus Rafinesque) are a large-bodied fish highly valued and commercially exploited across most of their range. Despite this, relatively little is known of their population demographics compared to other exploited species. To fill these knowledge gaps, we analyzed two independent long-term datasets (30 and 57 years, respectively) and population demographic data (age structure, growth, mortality, age at maturity, and recruitment) from multiple pools of the Upper Mississippi River System (UMRS) and Illinois River (Illinois, USA). Long-term data (30-year dataset) generally show downward trends or significant declines in catch per unit effort in the UMRS, while the 57-year dataset shows a stable trend or a significant increase in the Illinois River. The oldest smallmouth buffalo were estimated to be 39 years old, with nearly every pool sampled having individuals estimated to exceed 30 years of age. Except for Pool 13 of the UMRS, 90% of smallmouth buffalo were estimated to mature between 411 and 470 mm in length or between 8.7 and 11.2 years old. Recruitment was variable: strong year classes were generally preceded by multiple years of weak year classes. Our results indicate that the smallmouth buffalo population may be stable in portions of the UMRS and Illinois River systems, but significant declines in the northern extent of the UMRS may warrant conservation concern. Recent research into ages of buffalofishes shows that consideration should be given to the idea that the UMRS population could be age truncated. Results also emphasize the importance of long-term data and the ability to show changes in exploited populations over time.

Reduction of large vessel traffic improves water quality and alters fish habitat-use throughout a large river - Michael J. Spear; Brandon S. Harris; Taylor A. Bookout; Brian S. Ickes; Kathi Jo Jankowski; Levi E. Solomon; Kristopher A. Maxson; Andrya L. Whitten Harris; Andrew T. Mathis; Sam J. Schaick; Jesse A. Williams; Jason A. DeBoer; et al. (Science of The Total Environment, 2024)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

A field test on the effectiveness of milfoil weevil for controlling Eurasian watermilfoil in Wisconsin lakes - John E. Havel; Susan E. Knight; Kristopher A. Maxson (Hydrobiologia, 2017)